How does diabetic peripheral neuropathy impact patients' burden of illness and the economy? A retrospective study in Beijing, China - Pan, Qi; Fei, Sijia; Zhang, Lina; Chen, Huan; Luo, Jingyi; Wang, Weihao; Xiao, Fei; Guo, Lixin (Frontiers in Public Health, 2023)
Objective: Diabetic peripheral neuropathy (DPN) carries a heavy burden of illness for patients and negatively affects the economy. The objective of this study is to evaluate the cost and quantity of antidiabetic drugs needed in patients with or without DPN, as well as their variation trends in Beijing between 2016 and 2018. Methods: This observational cross-sectional study used data on diabetic patients with outpatient medication records obtained from Beijing Medical Insurance from 2016 to 2018. The medications, comorbidities, diabetes-related complications, treatment strategies, and costs of drug treatment were compared between DPN patients and non-DPN patients. Results: Of the 2853036 diabetic patients included in the study, 375216 (13.15%) had DPN, and 187710 (50.03%) of the DPN patients were women. Compared with non-DPN patients, DPN patients used more mediations (4.7±2.47 vs. 3.77±2.32, p<0.0001, in 2018) to treat related complications and comorbidities (2.03±1.2 vs. 1.71±1.05; 2.68±1.93 vs. 2.06±1.86, p<0.0001, respectively, in 2018). The total annual costs of drug treatment were higher in DPN patients than in non-DPN patients (¥12583.25 ± 10671.48 vs. ¥9810.91 ± 9234.14, p<0.0001, in 2018). The usage of DDP4i increased from 2.55% to 6.63% in non-DPN patients and from 4.45% to 10.09% in DPN patients from 2017 to 2018. Conclusions: The number of comorbidities, diabetic complications, medications, and annual drug treatment costs was greater in DPN patients than in non-DPN patients.